1987
DOI: 10.1073/pnas.84.22.8075
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional structure of an antibody-antigen complex.

Abstract: We have determined the three-dimensional structure of two crystal forms of an antilysozyme Fab-lysozyme complex by x-ray crystallography. The epitope on lysozyme consists of three sequentially separated subsites, including one long, nearly continuous, site from Gln-41 through Tyr-53 and one from Gly-67 through Pro-70. Antibody residues interacting with lysozyme occur in each of the six complementaritydetermining regions and also include one framework residue. Arg-45 and Arg-68 form a ridge on the surface of ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
233
0

Year Published

1992
1992
1997
1997

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 540 publications
(253 citation statements)
references
References 22 publications
20
233
0
Order By: Relevance
“…While loop 3 was identified by the escape mutations, no such mutations have been found on loops 1 or 2, which participate in the remainder of the footprint on symmetry-related VP2 subunits. This is consistent with the study of lysozyme-Fab complexes, where mutations have identified only a select subset of interface residues [18,19]. It is also consistent with studies of Reynolds et al [21] who showed that restrictions of the viability of polioviruses containing mutations within an antigenic site limit the range of escape mutations which can be observed by normal selection procedures.…”
Section: The Fab Footprint On the Viral Surfacesupporting
confidence: 79%
See 1 more Smart Citation
“…While loop 3 was identified by the escape mutations, no such mutations have been found on loops 1 or 2, which participate in the remainder of the footprint on symmetry-related VP2 subunits. This is consistent with the study of lysozyme-Fab complexes, where mutations have identified only a select subset of interface residues [18,19]. It is also consistent with studies of Reynolds et al [21] who showed that restrictions of the viability of polioviruses containing mutations within an antigenic site limit the range of escape mutations which can be observed by normal selection procedures.…”
Section: The Fab Footprint On the Viral Surfacesupporting
confidence: 79%
“…This compares well with the lysozyme surface area that is buried when complexed with HyHEL-5 [18,19]. In general, Fab-protein contacts cover surface areas of between 690Å 2 and 916Å 2 using a 1.7Å probe [20].…”
Section: The Fab Footprint On the Viral Surfacesupporting
confidence: 50%
“…Interestingly, using volumes to obtain ASP values (cal/A3) produces the best correlation, suggesting that cavity formation is an important parameter in calculating the free The experimental association energies were obtained from the literature. a, Vincent and Lazdunski (1972); b, Vincent et al (1974); c, Chen and Bode (1983); d, Hass and Ryan (1980); e, Bunting and Myers (1975); f, Read et al (1983); g, Ascenzi et al (1988); h, Empie and Laskowski (1982); i, Bode (1979) and Bolognes et al (1982); j , Pekar and Frank (1972); k , Akasaka et al (1982); I, Sheriff et al (1987); m, Ross et al (1977). Chothia and Janin (1975) first suggested that the free energy of association was related to the amount of surface area that was buried in the interface.…”
Section: Resultsmentioning
confidence: 99%
“…1B). The amide group of the adjacent framework residue Gln 90, the only L3 key residue present in CRIS-1, forms four hydrogen bonds: three with main-chain atoms from residues 92,93, and 94, and one with Oy from side chain of Thr 97 (Suh et al, 1986), and HyHel-5 (Sheriff et al, 1987), which represent, respectively, canonical forms 1, 2, and 3 for this hypervariable region. As a reference, the side chain of residue 90 is also shown in some detail.…”
Section: Resultsmentioning
confidence: 99%